2020
DOI: 10.4018/ijthi.2020100102
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Intention to Use Mobile Technology in Language Teaching

Abstract: This study aimed to qualitatively investigate the factors that influence teachers' behavioral intention to use mobile technology (BIU) for language teaching employing the original technology acceptance model (TAM) as a framework. Semi-structured interviews were conducted with 28 Arabic and English teachers. The study results revealed that there were several external variables influencing teachers' behavioral intention to use mobile technology. It was also found that participants had mixed levels of perceived e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Our research revealed that students' autonomous motivation did not significantly change when they were using MS Teams, which may be due to the fact that students' motivation to learn English is primarily influenced by their future and their career opportunities (at least according to what they perceive to be the case). However, autonomy and competence were found to have slightly increased when using the Microsoft Teams application because it may have opened up a new window in which to enjoy the language lessons that traditional teaching could not achieve (Aburezeq, 2013). Studies like these are needed today (particularly during/post pandemics like COVID-19), due to the usage of various instant messaging tools, most institutes are now providing distance learning and blended language learning.…”
Section: Discussion and Recommendationmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research revealed that students' autonomous motivation did not significantly change when they were using MS Teams, which may be due to the fact that students' motivation to learn English is primarily influenced by their future and their career opportunities (at least according to what they perceive to be the case). However, autonomy and competence were found to have slightly increased when using the Microsoft Teams application because it may have opened up a new window in which to enjoy the language lessons that traditional teaching could not achieve (Aburezeq, 2013). Studies like these are needed today (particularly during/post pandemics like COVID-19), due to the usage of various instant messaging tools, most institutes are now providing distance learning and blended language learning.…”
Section: Discussion and Recommendationmentioning
confidence: 99%
“…Among the many mobile learning subject areas, mobile-assisted language learning focuses on how various technologies can be used to enhance the learning process in order to motivate students (Aburezeq, 2013;Al Mansoori et al, 2022). Learning theories and practices within such a pedagogical framework are also influenced by the social and psychological development of individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overwhelming urge toward distance education, as a result of the closure of Universities and colleges, hastened the use of technology by teachers despite the factors that may hinder their adoption of new technology. These factors as they have been referred to in the existing literature concern teachers' attitudes, readiness, acceptance, resistance, self-efficacy perceptions, perceived usefulness, perceived ease of use, and behavioral intentions (See e.g., Aburezeq et al, 2020;Agbatogun, 2014;Cox, 2003;Demetriadis et al, 2003;Kao zt al., 2020;Perkins & McKnight, 2005;Sofronova, 1995;Teo et al, 2008). It can be noticed that the context of emergency online teaching during the pandemic altered the normal longitudinal teachers' perceptions, preparation, and readiness to use technology to the extent of generating new optimistic sentiments like humility, enthusiasm, and empathy between teachers and students (Cutri, Mena, & Whiting, 2020).…”
Section: Introductionmentioning
confidence: 99%